Longitudinal Investigation of Rehospitalization Patterns in Spinal Cord and Traumatic Brain Injury among Medicare Beneficiaries - Pretz, Christopher R. (Arch Phys Med Rehabil, 2017)
OBJECTIVE: To model 12-month rehospitalization risk among Medicare beneficiaries receiving inpatient rehabilitation for SCI or TBI and to create two (SCI- and TBI-specific) interactive tools enabling users to generate monthly projected probabilities for rehospitalization based on an individual patient’s clinical profile at discharge from inpatient rehabilitation. DESIGN: Secondary data analysis. SETTING: More than 1,100 inpatient rehabilitation facilities across the US. PARTICIPANTS: Medicare beneficiaries receiving inpatient rehabilitation for SCI or TBI. MAIN OUTCOME MEASURE: Monthly rehospitalization (yes/no) based on Medicare claims. RESULTS: Results are summarized through computer-generated interactive tools, which plot individual level trajectories of rehospitalization probabilities over time. Factors associated with the probability of rehospitalization over time are also provided, with different combinations of these factors generating different individual level trajectories. Four case studies are presented to demonstrate the variability in individual risk trajectories. Monthly rehospitalization probabilities for the individual high-risk TBI and SCI cases declined from 33–15% and 41–18%, respectively, over time, whereas the probabilities for the individual low-risk cases were much lower and stable over time: 5–2% and 6–2%, respectively. CONCLUSION: Rehospitalization is an undesirable and multifaceted health outcome. Classifying patients into meaningful risk strata at different stages of their recovery is a positive step forward in anticipating and managing their unique healthcare needs over time.